PERBANDINGAN SISTEM PENDIDIKAN DI NEGARA MAJU DAN BERKEMBANG DALAM ERA GLOBALISASI - Ana Tiara Syalwa; Afi yatun Kholifah (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Education is an important element in shaping the quality of human resources and determining a country's competitiveness in the era of globalization. Developed countries such as Australia have successfully implemented a structured, inclusive, and adaptive education system in line with technological developments, while developing countries such as Indonesia still face challenges in the form of unequal access, uneven teacher quality, and suboptimal curriculum implementation. This study aims to analyze the differences between the education systems of developed and developing countries through a review of the structure of education, the principles of implementation, the implementation of the curriculum, and the main problems faced. The method used is a literature study by collecting literature from books, scientific journals, and credible academic sources, which are then analyzed descriptively and qualitatively to obtain a comprehensive picture of the potential for developing the education system. The results of the study show that developed countries excel in education funding, teacher quality, competency-based curricula, and technology integration, while developing countries are still constrained by limited infrastructure, uneven teacher competency, and access gaps between urban and rural areas. A comparison with the Australian education system indicates that the principles of inclusivity, curriculum flexibility, stakeholder collaboration, and continuous evaluation can serve as strategic references for Indonesia in improving the quality of its education. Thus, education reform in developing countries can be more effective through strengthening teacher competencies, increasing funding, modernizing the curriculum, and equalizing infrastructure to realize quality, relevant, and sustainable education.